Peran Guru Dalam Pembiasaan Sholat Berjamaah - izzah, lathifatul; Purwaningsih, Ratna (Universitas Alma Ata, 2017)
Article is the result of field research (field research) using qualitative methods. This article tries to explain about the kind of worship prayer in congregation usually done in public madrasah tsanawiyah (MTs N) Galur Kulon Progo DIY, also will be to explain about the role of teachers in the habit of worship prayer in congregation for students in MTs N Galur Kulon Progo DIY. Thus the conclusion of this article mention that this type of regular daily prayers in congregation is held in the MTs N is Dhuha prayer, prayer Dhuhr, and Friday prayers. The role of teachers in habituation prayer in congregation MTs N is as educators, teachers, tutors, mentors, models and example, transfer camp, as well as generating the view.Keywords : The role of teacher, habit of worship prayer, the worship congregation